2017
DOI: 10.1007/s00221-017-4932-5
|View full text |Cite|
|
Sign up to set email alerts
|

tDCS application over the STG improves the ability to recognize and appreciate elements involved in humor processing

Abstract: The superior temporal gyrus (STG) has been found to play a crucial role in the recognition of actions and facial expressions and may, therefore, be critical for the processing of humorous information. Here we investigated whether tDCS application to the STG would modulate the ability to recognize and appreciate the comic element in serious and comedic situations of misfortune. To this aim, the effects of different types of tDCS stimulation on the STG were analyzed during a task in which the participants were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…We believe that this insight solution effect is due to the rATL's role in semantic integration, necessary to achieve global coherence during reasoning and discourse processing 25 . Following this idea, other studies indicate that right hemisphere semantic processing contributes to understanding novel metaphoric expressions, implicit comprehension, and humor [28][29][30][31]71 .…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…We believe that this insight solution effect is due to the rATL's role in semantic integration, necessary to achieve global coherence during reasoning and discourse processing 25 . Following this idea, other studies indicate that right hemisphere semantic processing contributes to understanding novel metaphoric expressions, implicit comprehension, and humor [28][29][30][31]71 .…”
Section: Discussionmentioning
confidence: 89%
“…RATL activity is thought to underlie the semantic integration of distantly related associations that contribute to language comprehension 25 and to creative problem-solving 17,26 , a characteristic that makes this brain area a potential key region for facilitating insight if stimulated. Other studies support the idea that right temporal semantic processing appears to contribute to understanding metaphors 27 , is involved in the development of distant semantic relations, humor and other forms of implicit comprehension [28][29][30][31] .…”
mentioning
confidence: 71%
“…Community cultural psychology is its sustainable development. The root of [15]. The virtual learning community provides people with a more free and harmonious multi-user learning environment.…”
Section: Virtual Learning Modelmentioning
confidence: 99%
“…In fact, previous evidences revealed that this type of non-ToM humorous stimuli (i.e. slapstick humor) involves the recruitment of other areas such as the superior temporal sulcus, the superior temporal gyrus, the middle occipital gyrus, and the precuneus (Manfredi et al, 2017;Samson et al, 2008;Watson et al, 2007) and involves cognitive mechanisms that are different from those involved in ToM humorous stimuli. For example, this type of humor is often labeled as aggressive or disparaging humor in the literature (Ferguson & Ford, 2008;Ford & Ferguson, 2004;Zillman, 1983).…”
Section: Post-hoc Comparisons Across the Tdcs Conditionsmentioning
confidence: 99%
“…The task was programmed using the E-prime 2.0 software package. The participants viewed the stimuli on a high-resolution VGA computer screen located at a distance of 50 cm from them (see Manfredi et al, 2017). Each strip was presented panel by panel at the center of the computer screen.…”
Section: Task and Proceduresmentioning
confidence: 99%